O uso da tecnologia Blockchain em Smart Cities: uma proposta para cidades inteligentes autopoieticas - Migliorini, Isabella Barella (2020)
Smart cities are an alternative to the process of political, economic, social and environmental transformation. The smart city overcomes the challenges of the past, makes the present better and prepares for the future, using technology to efficiently provide urban services and improve citizens' quality of life. The autopoietic smart city, with a focus on people, takes a systemic and dynamic approach through technologies such as blockchain. The rankings of smart cities help to verify which cities are standing out in different dimensions, factors or thematic areas. The selected indicators must be relevant so that the city portrait is the closest to reality. The smart city presents a dynamic reality with a large volume of data and areas of knowledge to be considered. The concept of Urban Autopoiesis made it possible to deal with these various dimensions of smart cities, as Maturana and Varela's autopoietic systemic approach enables the visualization of a smart city model based on the organic view. Blockchain technology enables very good results in the articulation of the autopoietic, self-regulating and sustainable smart city. In the collection of data on the degree of applicability of the blockchain, carried out with market experts in the use of this technology, it was possible to identify that the application of the blockchain has greater emphasis on the Brain and less emphasis on the Locomotor System of cities